An Analysis of the Development and Regulatory Framework of Cryptocurrency in Uganda - Douglas Dusabe Ngororano (Uganda Christian University, 2025)
This paper examines the development and regulatory framework of cryptocurrencies in Uganda, tracing the global and regional emergence of digital currencies and assessing Uganda’s response within its unique socio-economic and institutional context. With growing crypto adoption driven by youth entrepreneurship, digital freelancing, and cross-border payments, Uganda stands at a critical juncture, weighing significant opportunities against inherent risks. The study explores non-legal aspects, analysing public awareness, societal impacts, and challenges such as consumer vulnerability, digital exclusion, and market volatility, while highlighting advancements in digital finance, blockchain innovation, and youth-led start-ups. The analysis also scrutinizes Uganda’s legal and regulatory landscape, emphasizing the roles of institutions like the Bank of Uganda, the Financial Intelligence Authority, and the Uganda Revenue Authority. It finds that the lack of a comprehensive regulatory framework creates legal uncertainty, increasing fraud risks and hindering innovation. The paper advocates for a balanced regulatory approach, including enhanced public education, regulatory sandboxes, and regional collaboration, to foster responsible cryptocurrency adoption. This work contributes to the broader discourse on digital finance governance in emerging economies.
Under Graduate